Co-Reflective System: Supporting Collaborative Critical Thinking and Knowledge Building - Maimoona Salam; Dayang Hanani Abang Ibrahim; Dayang Nurfatimah Awang I skandar (International Journal of Innovation in Enterprise System, 2019)
Service-learning pedagogy provides practical learning experience for students by integrating community service with academic learning. However, experience is not enough, reflection on that experience is essential to produce new understanding. The concept of collaborative reflection has been recognized recently however, there is lack of research on how to structure guided collaborative reflection to view the process of knowledge building and how technologies can support it. To shed light on this issue, this study proposed a computational workflow of structured collaborative reflection which is adopted from integrated collaborative reflection model and implement a prototype (i.e. named as ‘Co-Reflective’) to proof the concept how Computer Supported Collaborative Reflection System (CSCRS) is supporting collaborative critical thinking and knowledge building. For this purpose, design science research methodology was employed in this study. The evaluation of Co-Reflective is provided where we asked our participants to evaluate their experience and give feedback about system. Based on the positive feedback of participants we conclude that Co-Reflective can effectively support for guided collaborative reflection activities to promote collaborative critical thinking and knowledge building. Implementation of Co-Reflective not only addresses the limitations of current technologies but also contribute in the body of knowledge by presenting the concept of integrated collaborative reflection model that promotes collaborative critical thinking and knowledge building. Keywords—collaborative knowledge building, collaborative reflection, Computer Supported Collaborative Reflection System (CSCRS), service learning.